Reverse-Phase HPLC Method for the Estimation of Selegiline Hydrochloride in Pharmaceutical Dosage Forms - Krishnaiah, Y.S.R.; Jayaram, B.; Rama, B.; Raju, V.; Bhaskar, P.; Murali Mohan Rao, P. (Asian Journal of Chemistry, 2010)
A rapid and sensitive high-performance liquid chromatographic method was developed for the estimation of selegiline hydrochloride in pharmaceutical dosage forms. Selegiline hydrochloride was chromatographed on a reverse phase C-18 column using ondansetron hydrochloride as internal standard in a mobile phase consisting of methanol and water in the ratio of 70:30 v/v. The mobile phase was pumped at a flow rate of 1 mL/min, and the eluents were monitored at 206 nm. The calibration curve was linear in the range of 0.2 to 20 μg/mL. The intra- and inter-day variation was found to be less than 1 % showing high precision of the assay method. The mean recovery of the drug from the solution containing 5 μg/mL was 98.47 ± 0.37% indicating high accuracy of the proposed HPLC method. Due to its simplicity, rapidness, high precision and accuracy, the proposed HPLC method may be used for determining selegiline hydrochloride in bulk drug samples or in tablets.